Two-year follow-up of the COVID-19 pandemic in Mexico - Loza, Antonio; Wong-Chew, Rosa María; Jiménez-Corona, María-Eugenia; Zárate, Selene; López, Susana; Ciria, Ricardo; Palomares, Diego; García-López, Rodrigo; Iša, Pavel; Taboada, Blanca; Rosales, Mauricio; Boukadida, Celia; et al. (Frontiers in Public Health, 2023)
Background: After the initial outbreak in China (December 2019), the World Health Organization declared COVID-19 a pandemic on March 11th, 2020. This paper aims to describe the first two years of the pandemic in Mexico. Design and methods: This is a population-based longitudinal study. We analyzed data from the national COVID-19 registry to describe the evolution of the pandemic in terms of the number of confirmed cases, hospitalizations, deaths and reported symptoms in relation to health policies and circulating variants. We also carried out a logistic regression to investigate the major risk factors of the disease severity. Results: From March 2020 to March 2022, the coronavirus disease 2019 (COVID-19) pandemic in Mexico underwent four epidemic waves. Out of 5,702,143 confirmed cases 655,524 were hospitalized (11.5%) and 314,680 (5.5%) died. Even if there is no difference in susceptibility by gender, males have a higher risk of death (CFP: 7.3% vs. 4.2%) and hospital admission risk (HP: 14.4% vs .9.5%). Severity increased with age. With respect to younger ages (0-17 years), the group of 60+ years or older reached adjusted odds ratios of 9.63 in case of admission and of 53.05 (95% CI: 27.94-118.62) in case of death. The presence of any comorbidity more than doubled the odds ratio, with hypertension-diabetes as the riskiest combination. While the wave peaks increased over time, the odds ratios to develop a severe disease (waves 2,3,4 to wave 1) decreased to 0.15 (95% CI: 0.12-0.18) in the fourth wave. Conclusion: The health policy promoted by the Mexican government decreased hospitalizations and deaths, particularly among older adults with the highest risk of admission and death. Comorbidities augment the risk of developing severe illness, which is shown to rise by double in the Mexican population, particularly for those reported with hypertension-diabetes. Factors such as the decrease in the severity of the SARS-CoV2 variants, changes in symptomatology, and advances in the management of patients, vaccination, and treatments, influenced the decrease in mortality and hospitalizations.